A forest of studies - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Eight forestry training institutes four in Cameroon, the others in the Central African Republic, Congo, Democratic Republic of Congo, and Gabon extended their harmonisation of curricula, research and communication in March 2002. They also...